Entrepreneurial Orientation and Business Performance of SMEs in Kathmandu - Goet, Joginder; Kharel, Kiran (Management Dynamics, 2023)
The study examines the impact of entrepreneurial orientation (EO) on the performance of small and medium-sized enterprises (SMEs) in Kathmandu. It emphasizes the key role of entrepreneurial orientation components such as autonomy, risk-taking, networking, pro-activeness, and innovation in shaping business performance. In this study, descriptive and causal-comparative research design has been utilized. The data was collected from 400 SMEs using structured questionnaires. The findings reveal that autonomy, risk-taking, networking, and innovation have significant positive effects on SME performance, with networking showing the strongest impact. However, pro-activeness did not significantly influence performance. These insights suggest that fostering autonomy, encouraging risk-taking, building strong networks, and promoting innovation are crucial for enhancing the business performance of SMEs. The study underscores the need for SMEs in Kathmandu to encircle entrepreneurial characteristics to continue competing and achieve sustained growth in a globalized environment.